2019
DOI: 10.1080/14767058.2019.1567707
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight in Jordan: a hospital-based study

Abstract: Background: Low birth weight (LBW) is one of the leading causes of neonatal and infant morbidity and mortality. Objective: To determine the prevalence and possible risk factors associated with LBW in four regional hospitals in Jordan. Methods: This retrospective study analyzed the medical records of all singleton live births for the period 2011-2015. Results: A total of 22,789 singleton live births were included for this study. Of these, 4133 (18%) had a LBW. Rates of LBW increased over the 5 years study perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“… 27 Maternal-related variables such as maternal age, maternal nationality, mode of delivery (vaginal, caesarean) and neonatal-related variables such as infant sex were significantly associated with LBW. 28 Mohammed et al 29 reported findings of LBW-related influences including preterm birth, pregnancy complications or comorbidities, advanced maternal age (≥35 years), first-born infants and female infants in the Jordanian region were similar. Similarly, Kim et al 30 revealed some Korean perinatal factors including preterm birth rate, LBWI, multiple births and maternal age were related to mean weight.…”
Section: Discussionmentioning
confidence: 93%
“… 27 Maternal-related variables such as maternal age, maternal nationality, mode of delivery (vaginal, caesarean) and neonatal-related variables such as infant sex were significantly associated with LBW. 28 Mohammed et al 29 reported findings of LBW-related influences including preterm birth, pregnancy complications or comorbidities, advanced maternal age (≥35 years), first-born infants and female infants in the Jordanian region were similar. Similarly, Kim et al 30 revealed some Korean perinatal factors including preterm birth rate, LBWI, multiple births and maternal age were related to mean weight.…”
Section: Discussionmentioning
confidence: 93%
“…Güney Çin'de, 2005-2017 yıllarını kapsayan bir çalışmada bu oran yaklaşık %8 olarak bulunmuştur (Rao et al, 2018). Ürdün'de 2011-2017 yılları arasında gerçekleştirilen bir araştırmada bu oranın %18 olduğu saptanmıştır (Mohammed et al, 2020). Tanzanya'daki bir çalışmada ise düşük doğum kilosu oranının %21 olduğu ifade edilmiştir (Kamala et al, 2018).…”
Section: Düşük Doğum Kilosuunclassified